Pattern of Viruses among the Jaundiced Patients Admitted in a Tertiary Care Hospital Chattogram, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Jaundice is the commonest presenting features of hepatitis and it is a common clinical condition in Bangladesh. As a country of the Asia Pacific region Bangladesh is considered to be a high risk country for developing hepatitis by differ ent hepatotropic viruses. This study represents the patterns and types of viruses among the patients admitted in a tertiary care hospitals in Bangladesh who were presented with jaundice. Materials and methods: Present cross sectional observational study done during a one year study period from July 2022 to June 2023 in a tertiary care hospital, Chattogram, Bangladesh among 114 patients. All patients who had clinical jaundice or having serum bilirubin > 2 mg/dl were recruited in the study. Clinical data were collected from all of them and viral serology were also done by ICT or ELISA. Informed written consent were taken from all patients and permission for the study were taken from ERB of the medical college. Results: Among 114 study subjects, male were 73(64%) and female were 41(36%) and male to female ratio was 1: 0.56. Among all, maximum were in the age range of